3D instability analysis of an underground geological repository—an Indian case study - Verma A.K.; Bajpai R.K.; Singh T.N.; Narayan P.K.; Dutt A. (My University, 2025)
Abstract Conceptual geological repositories are generally used for disposing spent nuclear wastes containing both high and low level of nuclear radiation and heat. Due to its long-lasting effect, it is imperative to analyze its long-term effect on the surrounding rock. Before analyzing radiation and thermal effect, it is important to have structurally stable cavern because designing an opening in rock is a more difficult problem than designing the structure made of steel. Underground rocks are under stress because of the weight of the overlying rock, and in addition, an underground opening will produce a stress concentration and stress relaxation in the surrounding rock. If the induced stress in the surrounding rock exceeds its strength, the opening will fail either by fracturing or by deforming more than the tolerable limit. In this paper, the stability of four different shapes of excavation has been examined for conceptual geological repositories in Indian context. This has been done using equivalent continuum numerical model which has been incorporated in the commercial finite difference code-FLAC-3D. Effects of opening shapes on stress distribution, subsidence of crown and side wall, and their stability have been analyzed and discussed. The validation of FLAC3D software for its applicability in conceptual underground geological repositories has been done with a published literature. ©Saudi Society for Geosciences 2010.